Multicytokine-producing CD4+ T cells characterize the livers of patients with NASH - Anna Woestemeier; Pasquale Scognamiglio; Yu Zhao; Jonas Wagner; Franziska Muscate; Christian Casar; Francesco Siracusa; Filippo Cortesi; Theodora Agalioti; Simone Müller; Adrian Sagebiel; Leonie Konczalla; et al. (JCI Insight, 2023)
A role of CD4+ T cells during the progression from nonalcoholic fatty liver disease (NAFLD) to nonalcoholic steatohepatitis (NASH) has been suggested, but which polarization state of these cells characterizes this progression and the development of fibrosis remain unclear. In addition, a gut-liver axis has been suggested to play a role in NASH, but the role of CD4+ T cells in this axis has just begun to be investigated. Combining single-cell RNA sequencing and multiple-parameter flow cytometry, we provide the first cell atlas to our knowledge focused on liver-infiltrating CD4+ T cells in patients with NAFLD and NASH, showing that NASH is characterized by a population of multicytokine-producing CD4+ T cells. Among these cells, only those with a Th17 polarization state were enriched in patients with advanced fibrosis. In parallel, we observed that Bacteroides appeared to be enriched in the intestine of NASH patients and to correlate with the frequency of multicytokine-producing CD4+ T cells. In short, we deliver a CD4+ T cell atlas of NAFLD and NASH, providing the rationale to target CD4+ T cells with a Th17 polarization state to block fibrosis development. Finally, our data offer an early indication to test whether multicytokine-producing CD4+ T cells are part of the gut-liver axis characterizing NASH.